Cybervictimization and Depression among Adolescents: Coping Strategies as Mediators - Siah, Poh Chua; Tee, Xiang Yi; Tan, Joaan Tjin Ai; Tan, Chee Seng; Komathi, Lokithasan; Low, Sew Kim; Yap, Chin Choo * (MDPI, 2022)
Studies have shown the relationships among cybervictimization, coping strategies, and depression, but no study has examined the mechanism that links the three variables. Accordingly, this study used the transactional model of stress and coping theory as a conceptual framework and proposed that coping strategies are mediators for the effects of cybervictimization on depression. A total of 387 adolescents were recruited by using the purposive sampling method. The results showed that cybervictimization is not directly associated with depression. All the coping strategies are found to be associated with cybervictimization, but only the avoidant coping strategy is the statistical mediator for the effects of cybervictimization on depression. This study's findings suggest that the transactional model of stress and coping theory may provide a framework in the area of cyberbullying and recommend more actions to be taken in order to reduce the use of avoidance coping strategies among victims of cyberbullying.